(untitled) (CIPEEX, 2025)
This exploratory study aims to analyze how professionals in financial institutions perceive the effects of technological innovation on their careers and work environment. The research adopts a quantitative approach, based on articles available in periodicals. Through this, it explored pertinent findings that examine the relationship between technological developments and future employment in the financial sector. The research data was collected using keywords related to the subject: Technological Innovation, Financial Institutions, Professionals’ Perceptions, Digital Transformation, in databases such as Scopus, Web of Science and SciELO. The analysis included collecting pertinent information on aspects such as the sample size, the methods used and the main results. In addition, the data was organized in such a way as to facilitate visualization and comparison using graphs and tables. The results show that professionals are thinking about the future of work with both hope and fear. They perceive that new technologies, such as process optimization and the creation of new positions and specializations, offer opportunities for professional growth and development. However, they fear the possibility of losing their jobs due to automation and the constant need for knowledge and skills.